AN ASSESSMENT OF LAW FACULTY STUDENTS' COMPREHENSION LEVELS OF THE LANGUAGE OF CORPORATE TAX LAW - Cem Barlas Arslan (International Online Journal of Education and Teaching, 2016)
The purpose of this study is to analyze the language structure of tax laws within the scope of ongoing tax complexity in the Turkish law system. Using the qualitative case-study research format, this study included 295 third and fourth year students at Kirikkale University Law Faculty in the spring term of 2015. Participating students were asked for synonyms/meanings of eleven terms which were selected from the Corporate Tax Law that came into force being prepared in the earliest time as a general qualified tax law among tax laws to test the students’ knowledge of the language structure of the aforesaid law.  The assessment showed that a substantial section of these Law students did not know the meanings of these words.